DISEÑO ARQUITECTÓNICO DE UN CENTRO GERONTOLÓGICO PARA EL CANTÓN SAMBORONDÓN, PARROQUIA LA PUNTILLA. - Oneto Trujillo, Santiago Gabriel. (2022)
Due the progressive increase in the population of older adults in Ecuador, it is necessary to design projects that involve their priority attention to guarantee a dignified life. The architectural solution that has been developed meets this growing demand for specialized spaces for older adults with the aim of providing quality services to this citizens that traditionally does not have enough infrastructure or quality projects. The creative process of the project was inspired by the transformation to which the bones of the human being are subjected, in an analogy of growth and evolution that reaching this stage of life means. Based on this creative exercise, a series of design processes were developed that allowed the creation of a language that has been used throughout the architectural design process. The general scheme of the project has been design based on a central space around which various spaces dedicated to the care of older adults were organized and which are also articulated with the re sidence service. This typology with its uses and areas, were obtained throught study of cases, endorsed by a survey of potential users. One aspect that has been involved is the design under bioclimatic criteria. In this way, there is a building that responds efficiently to the climate where the project is located. The ultimate goal of this architectural project is to put a solution to society’s consideration that allows to attend and develop the potential and self-esteem of the elderly of Guayaquil and Samborondón